PENGGUNAAN METODE GASING UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL GERAK LURUS DI SMA NEGERI 3 SANGGAU - Ahmad Fauzi Ananda; Tomo Djudin; Syaiful B Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis purpose of this research to see the effectiveness of the influence of gasing methods in improving  students’ ability to solve the problem of Motion Straight in class X IPA SMA Negeri 3 Sanggau. The research method used Pre-Experimental design with One Group Pre-Test Post-Test design. The data collection tool is an essay test with a reliability level of 0.55 (Alpha). The research sample are 34 students. The average of students 'ability during the initial test was 24.05, while the average of students' ability after learning using the gasing method increased to 65.66. Result of data  analysis with test of wilcoxon got value  equal to -5,086. Since  is located outside the acceptance area of Ho (-1.96≤ Z ≤ 1.96), there is a significant score difference between before and after remediation using the gasing method. the used of gasing methods is an effective to improve students' ability to solve the problem with the criteria effect size that is equal to 1.6 (high category). This study is expected to be used as an alternative learning activities to improve students' ability in solving problems.Keywords: Poblem Solving ability, gasing methode, Motion Straight